Individual lifestyle profile of first-year dental students from the University of Aracatuba, Brazil - 2015 - Saliba, Tânia Adas; de Sandre, Amanda Santos; Saliba Moimaz, Suzely Adas; Saliba Garbin, Clea Adas (Universidad y Salud, 2017)
Introduction: Lifestyle is a factor related to the wellbeing of the individual which alters his or her morbidity and mortality. Objective: To analyze the lifestyle of young people who entered the dentistry program in 2015 and its association with demographic factors. Materials and methods: A cross-sectional analytical observational study was conducted with 114 first-year dental students. The data were collected with two instruments: Individual Lifestyle profile (ILP) which evaluated nutrition, physical activity, preventative behavior, social relationship and stress control; and a validated questionnaire that included sociodemographic variables, working condition and the departure from home on the basis of entering higher education. Maximum likelihood statistical tests and U of Mann-Withney were applied, considering a significance α = 0.05. Results: The majority of participants were women with an average age of 20.06 (± 2.65) and 18.96 (± 1.78) in the night and day courses, respectively. 81.57%, left home to enter the university and 7% carried out a paid activity. They presented an undesirable lifestyle profile in relation to nutrition, physical activity and stress control. Nutrition was influenced by the socioeconomic profile (P = 0.014). The consumption of alcohol and tobacco (p = 0.017) and the time dedicated to rest (P = 0.018) were significantly higher in students of in the night program. Conclusion: The lifestyle of young people who entered dentistry was not the desirable one. Living away from parents and the financial dependency of students are factors that affect their lifestyle.